Comparing the Experience of and Factors Perpetuating Chronic Insomnia Severity Among Young, Middle-Aged, and Older Adults. (January 2021) - Sidani, Souraya; Ibrahim, Sarah; Lok, Jana; O'Rourke, Hannah; Collins, Laura; Fox, Mary
The prevalence of chronic insomnia is on the rise among young, middle-aged, and older adults. This secondary data analysis examined age-group differences in the experience of and factors perpetuating insomnia severity. Pretest data, obtained from a trial of behavioral interventions, were collected from 742 participants, using psychometrically sound measures of perpetuating factors (sleep habits, unhelpful beliefs, presleep arousal), insomnia experience (symptoms, perceived severity), and consequences or impact on daytime functioning. The age groups reported different insomnia symptoms (difficulty maintaining sleep in older adults) and impact on daytime functioning (poorer in older adults), but the same level of perceived insomnia severity. Unhelpful beliefs about sleep predicted insomnia severity in all age groups, and presleep arousal contributed to insomnia in young adults. The results highlight the importance of adequately managing chronic insomnia to minimize its impact on daytime functioning in all age groups, and of tailoring therapy to their experiences.